Milenial dan Seni Tradisi - Wiwin Indiarti; Hervina Nurullita (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
This article is based on the Community Partnership Program (PKM) which seeks to solve the problems faced by Osing ethnic group, in this case MLY Milenial, from the aspects of preservation strategies and revitalization of traditional art of Lontar Yusup reading session called mocoan. The solutions offered by this program are the procurement of mocoan costumes based on traditional Osing fabrics, procurement of Lontar Yusup learning materials / books for Mocoan Lontar Yusup training, procurement of violin instruments for mocoan accompaniment, and Mocoan Lontar Yusup training for young people. The activities are in the form of procuring mocoan costumes based on traditional Osing fabrics, procuring materials / learning books for Lontar Yusup for Mocoan Lontar Yusup training, procuring violin instruments for mocoan accompaniment, and Mocoan Lontar Yusup training for young people while the team continuously doing mentoring during the period of the PKM program. The outputs are articles in journals and seminars, printed mass media publications, videos of activities implementation and increased partner empowerment.